Integral Education: Founding Vision and Principles - Bahman A.K. Shirazi (Integral Review, 2011)
This introductory article gives a brief account of the founding vision and ontological and epistemological principles of the integral framework expounded by Haridas Chaudhuri and some of his original collaborators at the California Institute of Integral Studies (CIIS). A brief biographical account of Sri Aurobindo and Mother Mirra Alfassa, originators of integral yoga and education, is provided and some of the principle tenets of an integral worldview that informs the philosophy of integral education are discussed.